Does zakat impact poverty alleviation in Indonesia during Covid-19? - Zulyanto, Aan; Wiranatakusuma, Dimas Bagus; Abdullah, Naziruddin; Yusuf, Muhammad K; Aprizal, Anggi (Universitas Muhammadiyah Yogyakarta, 2025)
Zakat functions as a crucial instrument for achieving developmental goals, including the improvement of individual welfare. This study aims to analyse the effect of zakat, as measured by the National Zakat Index (NZI), on poverty alleviation in Indonesia during the Covid-19 pandemic. This research utilizes panel data from 32 Indonesia provinces covering the period from 2020 to 2022, employing the Fixed Effect Model (FEM) analysis method. The current analysis has not found a statistically significant effect of the National Zakat Index on the decrease of poverty rates in Indonesia. A major element to the enduring poverty in Indonesia is the inadequate collection of national zakat money. The Covid-19 pandemic has led to a significant rise in the number of individuals living in poverty, thereby decreasing zakat payment collections. The NZI is an extensive index that encompasses both macro and micro aspects. The NZI is expected to function as an objective metric for assessing the efficacy of zakat administration in Indonesia. The establishment of efficient zakat management is anticipated to enhance poverty reduction efforts. The policy consequence derived from the findings is to enhance zakat management organizations. This study contributes to the relationship between zakat and poverty reduction from a macro-level perspective, unlike earlier research that focuses on micro-level data.